DETERMINING THE NUMBER OF OCCUPIED PERSONS, NEEDED BY DAIRY CATTLE FARMS IN BULGARIA - Tsvetana HARIZANOVA – METODIEVA; Nikola METODIEV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of the study is to determine the number of occupied persons, needed by dairy cattle farms in Bulgaria. The information was collected through interview and the number of cows in the main herd, decares of arable land (own and rented) and the number of occupied persons, directly involved in the production process, were analyzed. A regression model was constructed with a confidence level of 95% using the Ordinary Least Squares Method. The regression model is as follows: L = C1.A + C2.D + C + a, where: L is natural logarithm of the the number of occupied persons, needed by dairy cattle farms; А is natural logarithm of the decares of arable land; D is natural logarithm of the number of dairy cows; C1 and C2 are the coefficients of the independent variables; С is a constant; a is an error of the regression. By replacing the constant and the coefficients with their theoretical values, it is obtained the following model: L = 0.067.A + 0.596.D - 1.386. The number of occupied persons could vary depending on the type of crops, the technology and the intensification of the production process. With the increase in the number of cows in the main herd and the amount of arable land, the number of occupied persons needed also increase. The constant in the regression model is a negative number (-1.386), which could be explained by better utilization of the working time: a major part of the occupied persons can perform activities related to dairy farming, and can also be included in forage production. It could be concluded that for a farm with 20 cows and 20 decares of arable land, the theoretical number of occupied persons is 1.8. A farm with 100 cows and 100 decares of arable land needs an average of 5.3 workers, but the number can vary between 3.8 and 6.8 workers. In a farm with 150 dairy cows and 3,000 decares of arable land needs an average of 8.5 workers. The combination of forage production and dairy cattle production leads to optimization of the number of occupied persons needed.